2009
DOI: 10.1089/apc.2009.0086
|View full text |Cite
|
Sign up to set email alerts
|

Health System and Personal Barriers Resulting in Decreased Utilization of HIV and STD Testing Services among At-Risk Black Men Who Have Sex with Men in Massachusetts

Abstract: Testing for HIV and other sexually transmitted diseases (STD) remains a cornerstone of public health prevention interventions. This analysis was designed to explore the frequency of testing, as well as health system and personal barriers to testing, among a community-recruited sample of Black men who have sex with men (MSM) at risk for HIV and STDs. Black MSM (n = 197) recruited via modified respondent-driven sampling between January and July 2008 completed an interviewer-administered assessment, with optional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
83
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 52 publications
(65 reference statements)
5
83
1
Order By: Relevance
“…Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 . Still, such differences may be due to the lack of a standardized period for which the number of partners was computed, varying widely in the literature, or to characteristics like the size of MSM social networks, age, schooling, and social class, factors that may be associated with the number of sexual partners in this sample.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 . Still, such differences may be due to the lack of a standardized period for which the number of partners was computed, varying widely in the literature, or to characteristics like the size of MSM social networks, age, schooling, and social class, factors that may be associated with the number of sexual partners in this sample.…”
Section: Discussionsupporting
confidence: 89%
“…Reporting a previous syphilis test was statistically associated with HIV infection and syphilis, as in other studies 24,28 , but it can also be associated with risky sexual practices for STI 24,27,28,41 .…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations